A model of an IoT system based on RFID tags for mine defense under war conditions and in the post-war period - Kolesnikova, Kateryna; Gladka, Myroslava; Kostikov, Mykola; Myronova, Natalia (My University, 2023)
Radio frequency identification (RFID) technology is widely used in various industries, including logistics, retail, healthcare, and agriculture. In recent years, RFID has also been explored for military and civilian applications, especially in wartime. RFID tags can be used to protect military and civilian population during war by providing real-time tracking of people, vehicles and equipment. The use of RFID tags in the military and defense complex is gaining great popularity [1, 2, 3], however, the use of RFID tags for mine security has not yet been fully explored. A separate important task under war conditions is the mine defense of territories where combat actions are taking place. The use of various mines to create blocking effects from the enemy ensures the security of territories in wartime and postwar times. The use of mines for the security of territories is known as "mine defense". This includes the placement of mines or explosive devices in a certain area or around important objects in order to protect these objects from possible threats. The main aspects of using mines for the security of territories include: the creation of minefields (placement of mines or explosive devices in a certain area to create a minefield that can become an obstacle for potential invaders or enemies); creation of maps of minefields (designation of minefields to inform own troops and the civilian population about their presence and location, to avoid danger). It is important to note that the use of mines for the security of territories must comply with international norms and conventions regarding the prohibition of the use of anti-personnel mines, and must also comply with the principles of humanitarian law to protect the civilian population and minimize humanitarian consequences. The use of RFID tags on mines is a solution that fully ensures the implementation of these norms and conventions. This article considers the use of RFID tags in wartime, the advantages of using RFID technology for the implementation of mine defense of territories, the rules for the protection of RFID tags used to ensure the safety of the military and civilian population.

Технологія радіочастотної ідентифікації (RFID) широко використовується в різних галузях, включаючи логістику, роздрібну торгівлю, охорону здоров’я та сільське господарство. В останні роки RFID також досліджується для військових і цивільних застосувань, особливо у воєнний час. RFID-мітки можна використовувати для захисту військових і цивільного населення під час війни, забезпечуючи відстеження людей, транспортних засобів і обладнання в реальному часі. Використання RFID-міток у військовому та оборонному комплексі набуває великої популярності [1, 2, 3], однак використання RFID-міток для безпеки шахт ще не повністю вивчено. Окремим важливим завданням в умовах війни є протимінна оборона територій, де ведуться бойові дії. Використання різноманітних мін для створення загороджувальних ефектів від противника забезпечує безпеку територій у воєнний і післявоєнний час. Використання мін для безпеки територій відоме як «мінна оборона». Це включає розміщення мін або вибухових пристроїв на певній території або навколо важливих об'єктів з метою захисту цих об'єктів від можливих загроз. До основних аспектів застосування мін для забезпечення безпеки територій належать: створення мінних полів (розміщення мін або вибухових пристроїв на певній території з метою створення мінного поля, яке може стати перешкодою для потенційних загарбників чи ворогів); створення карт мінних полів (позначення мінних полів для інформування власних військ і цивільного населення про їх наявність і розташування, щоб уникнути небезпеки). Важливо зазначити, що використання мін для безпеки територій має відповідати міжнародним нормам і конвенціям щодо заборони використання протипіхотних мін, а також має відповідати принципам гуманітарного права для захисту цивільного населення та мінімізувати гуманітарні наслідки. Використання RFID-міток на шахтах є рішенням, яке повністю забезпечує реалізацію цих норм і конвенцій. У статті розглянуто використання RFID-міток у воєнний час, переваги використання RFID-технології для реалізації протимінної оборони територій, правила захисту RFID-міток, які використовуються для забезпечення безпеки військовослужбовців та цивільного населення.
Keywords: IoT; RFID; identification; defense; war; military; civilian population; mine defense; security; safety; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки